2020
DOI: 10.1080/02670844.2020.1712062
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heat treatment on the properties of Co–P–TiO2 nanocomposite coatings

Abstract: The effects of heat treatment on the properties of electrodeposited Co-P-TiO 2 nanocomposite coatings were systematically investigated. The TiO 2 nanoparticles-reinforced Co-P-TiO 2 nanocomposites were heat-treated at different temperatures. Thermal analysis was conducted to characterize the structural transitions. The phase constituents and surface morphology of nanocomposites were identified. The mechanical properties including microhardness and wear tests were examined, and the electrochemical behaviour of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…With the increasing demand for protective coatings used in harsh working conditions, the co-deposition of second-phase particles into the nickel-based coatings provides a viable route to enhance the corrosion and tribological properties of the composite coatings [28][29][30]. These second-phase particles can be hard particles, such as Si 3 N 4 [31], Al 2 O 3 [32], TiO 2 [33], CeO 2 [34], SiO 2 [35] and SiC [36,37], which would enhance the wear resistance of nickel-based coatings. The reinforcements can either be lubricant particles, including MoS 2 [28], carbon nanotube [38], graphite [39], graphite oxide [37] et al which would decrease the friction coefficient of the composite coatings.…”
Section: Introductionmentioning
confidence: 99%
“…With the increasing demand for protective coatings used in harsh working conditions, the co-deposition of second-phase particles into the nickel-based coatings provides a viable route to enhance the corrosion and tribological properties of the composite coatings [28][29][30]. These second-phase particles can be hard particles, such as Si 3 N 4 [31], Al 2 O 3 [32], TiO 2 [33], CeO 2 [34], SiO 2 [35] and SiC [36,37], which would enhance the wear resistance of nickel-based coatings. The reinforcements can either be lubricant particles, including MoS 2 [28], carbon nanotube [38], graphite [39], graphite oxide [37] et al which would decrease the friction coefficient of the composite coatings.…”
Section: Introductionmentioning
confidence: 99%
“…Ardakani et al [24] found higher hardness and lower corrosion resistance using SiO 2 and Al 2 O 3 particles together in Ni–P coating on Al6061 substrate material. The use of TiO 2 particle-based coatings has found to be more effective in water and air remediation applications [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al [14] prepared a high-performance duplex-structured Ti/SnO 2 -Sb 2 O x -CNT composite anode using the electrodeposition method. In our recent studies, a sol-enhanced electrodeposition method has been proposed to efficiently dope inert nanoparticles and achieve their well-dispersion into the coating [15][16][17][18], which can serve as a promising method for Ti/SnO 2 -Sb 2 O x modification.…”
Section: Introductionmentioning
confidence: 99%